The Censorship of Misogynistic Rap Music - A Consideration of Gender-Based Harms and Free Speech - Tomlinson, Brendan H (Victoria University of Wellington Law Review, 1996)
The lyrics of gangster rap music have created a storm of controversy in the United States and elsewhere. This article considers the censorship of misogynistic rap music, analysing both the harm which it may do to women, and the way in which free speech principles apply to rap music. The criteria for works to be censored in New Zealand and the United States are analysed. Comments are made about how the New Zealand Classification Office should treat rap music works. It is argued that censorship of rap will rarely be justified. The article concludes by examining an interesting and fundamental difference between the free speech principles of the two jurisdictions: American free speech doctrine treats censorship based on the work's viewpoint with hostility, whereas New Zealand law advocates censorship of this kind.